User profiles with palliative care needs linked to a primary healthcare center in the city of Porto Alegre, RS - Bastos, Juliana Marques Coelho (2023)
Strengthening in Palliative Care (PC) in Primary Healthcare (PHC) increases the quality of care at the end of life and reduces complications from long hospitalizations. The objective of this work was to analyze data on mortality that occurred in patients with advanced chronic non-communicable diseases associated with the Vila Floresta Primary Healthcare Center of the Conceição Hospital Group (VFPHC-CHG) and to verify how many of these would be eligible to PC. It is a transverse, descriptive and quantitative and retrospective approach research. Data come from electronic health records, management monitoring report, VFPHC-CHG medical records and Porto Alegre Epidemiological Surveillance. The Palliative Care Screening Tool (PCST) scale for PC eligibility criterion. Out of a total of 155 people who died and lived in the VFPHC-CHG covered territory in 2019, 55.2% (n = 86) were female, 54.2% (n = 84) were elderly and more 80 years old, 23.9% (n = 37) had died within five years after diagnosis, in 69.7% (n = 108) of cases the place of death was the hospital, 66.5% (n = 103) had no medical record, were neoplasms the main causes of death in 34.8%(n = 54), and 42.6% (n = 66) were considered eligible for PC according to PCST. It is concluded that the profile of people with diagnosis for over five years of the disease that resulted in death could be observed more carefully by PHC teams regarding PC, increasing the search for those who are eligible and establishing effective communication with hospitals in care transfer.